Comparing the Outcomes of MSA and Fundoplication in Severe GERD. Issue 4 (December 2022) - Wang, Mark C.; Silva, Jack P.; James, Tayler J.; Rodriguez, Eddie A.; Cheng, Vincent; Putnam, Luke R.; Bildzukewicz, Nikolai A.; Bell, Reginald; Lipham, John C.
Introduction: Magnetic sphincter augmentation (MSA) is an effective treatment option for gastroesophageal reflux disease (GERD), with similar outcomes to fundoplication. MSA has yet to be compared to fundoplication specifically in patients with severe GERD. The objective of this study was to compare MSA and fundoplication in patients with severe GERD. Methods: A retrospective cohort study was performed of patients with severe GERD (preoperative DeMeester score >50) who underwent MSA or fundoplication at 3 high-volume centers from 2016 to 2019. Nissen and partial fundoplications were included. GERD control was measured by GERD health-related quality of life (GERD-HRQL) scores and discontinuation of acid suppressive medication (ASM). Other outcomes included postoperative gas-bloat symptoms, dysphagia requiring dilation, and esophagitis. Results: A total of 122 patients were included: 82 (67%) underwent MSA and 40 (33%) underwent fundoplication (23% Nissen, 77% partial). The groups were similar regarding gender, GERD duration, hiatal hernia size, preoperative GERD-HRQL score, severe esophagitis, and DeMeester score. Median follow-up was 24 [12-34] months. Postoperative GERD-HRQL scores (5 vs 3, P  = .36), ASM discontinuation (80% vs 86%, P  = .41), gas-bloat symptoms (18% vs 23%, P  = .58), dysphagia requiring dilation (19% vs 8%, P  = .11), and esophagitis (7% vs 10%, P  = .08) were similar between the groups. A subset analysis was performed comparing outcomes of MSA, Nissen fundoplication, and partial fundoplication. No significant differences were found. Conclusion: In this cohort of patients with severe GERD, MSA was just as effective as Nissen and partial fundoplication with regards to improved quality of life and side effect profile at 24-month follow-up.